EFFICIENCY OF MINDFULNESS BASED STRESS REDUCTION ASA METHOD FOR WORK-RELATED STRESS AND BURNOUT SYNDROME AMONG HEALTHCARE PROFESSIONALS. - Dareen Talal Garanbish, Ahmed Mohmmad Zuaer, Ahmed Ali Atiah Almalki, Waad Rafat Abdulaziz Edrees, Mohammed Abdulrazzag Hawsawi, Mohammed Ahmad Sharwani, Mamdouh Mastour Alharthi,; Amira Obeid Aljedani, Nawaf Anwar Omar Turkistani, Ali Ahmed Ali Alawi, Nada Saud Alrehaili, Tarfah Saleh Alanazi, Shouma Qayem Albalawi, Khadijah Saleem Alrowaili, Shuaa Saho Arfaj Alsirhani (Chelonian Research Foundation, 2022)
Healthcare professionals (HCPs) often face burnout and occupational stress. Research has shown that the practice of mindfulness-based stress reduction (MBSR) can enhance the psychological well-being of healthcare professionals (HCPs). Currently, systematic reviews and meta-analyses have mostly concentrated on empirical research that examine the effectiveness of Mindfulness-Based Stress Reduction (MBSR) in reducing stress among healthcare professionals (HCPs). These reviews are restricted to empirical studies published prior to December 2021. This systematic review sought to enhance the existing body of data and expand our comprehension of the efficacy of MBSR in enhancing the psychological functioning of healthcare professionals (HCPs)